2019
DOI: 10.1001/jamanetworkopen.2019.17043
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hospital-Based Specialty Palliative Care in the United States From 2013 to 2017

Abstract: This cohort study characterizes current practice and trends among patients cared for and outcomes achieved by inpatient specialty palliative care services in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 19 publications
4
43
0
1
Order By: Relevance
“…In Erlenwein's study, 24% of PCT patients were transferred to a palliative care unit (Erlenwein et al 2014), fewer than in Würzburg (30%). The range of deceased patients during PCT co-management is comparable to other studies: 20.3% in Schoenherr et al (2019) and 12% in Gaertner et al (2012).…”
Section: Team Composition Working Mode Patient Characteristics Andsupporting
confidence: 88%
See 4 more Smart Citations
“…In Erlenwein's study, 24% of PCT patients were transferred to a palliative care unit (Erlenwein et al 2014), fewer than in Würzburg (30%). The range of deceased patients during PCT co-management is comparable to other studies: 20.3% in Schoenherr et al (2019) and 12% in Gaertner et al (2012).…”
Section: Team Composition Working Mode Patient Characteristics Andsupporting
confidence: 88%
“…The German study of Erlenwein et al has shown that the PCT was contacted about 6–8 days after admission to hospital with a mean hospitalisation of 13–14 days (0–36 days in surgical departments, and 0–138 days in non-surgical departments, Erlenwein et al 2014 ). In the study of Schoenherr et al, PCT consultations were requested a mean of 4.8 days into the hospital stay (range 1.7–11.1 days, Schoenherr et al 2019 ). In Nagasaki the first PCT contact was earlier and also initiated for patients in better general condition, maybe due to the joint visits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations